Collagen Extraction from Bone of Lutjanus sp. and Toxicity Assay (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Indonesia is a maritime country with the potential fisheries resources. However, utilization only revolves around the meat, while other parts have not been used optimally, especially fish bones which have the potential to produce collagen, so it needs to be developed. The aims of this study ware extracted collagen from bone of Lutjanus sp. and determine its the Anticancer activity. The collagen was extracted by using hydroextraction method and identification by FTIR. The initial screening anticancer activity was done by using Brine Shrimp Lethality Test (BSLT) method for toxicity assay. The results showed that the yield of collagen was 4.535% with protein concentration was 8,815 mg/mL. Identified collagen from spectrum of amide A, B, I, II, and III at 3421.72; 2926.01; 1651.07; 1541.12; 1240.23 cm-1. The toxicity test was shown in LC50 values of  8,760 μg/mL. The collagen from Lutjanus sp. bone can be used as natural anticancer agent.
Keywords: Collagen; Lutjanus sp.; Bone; Anticancer; Hidroextraction; BSLT